Deficiency of ROS-Activated TRPM2 Channel Protects Neurons from Cerebral Ischemia-Reperfusion Injury through Upregulating Autophagy. (28th July 2021) - Hu, Xupang; Wu, Lijuan; Liu, Xingyu; Zhang, Yi; Xu, Min; Fang, Qiuyuan; Lu, Lin; Niu, Jianguo; Abd El-Aziz, Tarek Mohamed; Jiang, Lin-Hua; Li, Fangfang; Yang, Wei
Abstract : Cerebral ischemia-reperfusion (I-R) transiently increased autophagy by producing excessively reactive oxygen species (ROS); on the other hand, activated autophagy would remove ROS-damaged mitochondria and proteins, which led to cell survival. However, the regulation mechanism of autophagy activity during cerebral I-R is still unclear. In this study, we found that deficiency of the TRPM2 channel which is a ROS sensor significantly decreased I-R-induced neuronal damage. I-R transiently increased autophagy activity both in vitro and in vivo . More importantly, TRPM2 deficiency decreased I-R-induced neurological deficit score and infarct volume. Interestingly, our results indicated that TRPM2 deficiency could further activate AMPK rather than Beclin1 activity, suggesting that TRPM2 inhibits autophagy by regulating the AMPK/mTOR pathway in I-R. In conclusion, our study reveals that ROS-activated TRPM2 inhibits autophagy by downregulating the AMPK/mTOR pathway, which results in neuronal death induced by cerebral I-R, further supporting that TRPM2 might be a potential drug target for cerebral ischemic injury therapy.